Metodologia para análise da viabilidade técnica e econômica da troca de empilhadeiras à combustão por modelos elétricos - Copetti, Douglas Flores (2023)
In an increasingly global scenario guided by the imperative need to mitigate greenhouse gas emissions and the search for sustainable solutions, the industry faces the challenge of reconfiguring its logistics operations in an ecologically responsible manner. This study aims to be an instrument in this context, by examining the feasibility of transitioning from fossil fuel-powered forklifts to their electric equivalents. The research is anchored in a literature review about electric forklifts and the concept of energy transaction through electric vehicles. Furthermore, the potential to transact energy through electric forklifts is explored. In the conducted case study, a saving of R$ 1,865,653.37 was calculated through the replacement of leasing models powered by liquefied petroleum gas with electric forklifts equipped with lead-acid batteries. This data is complemented by a reduction of 2,646 tons of equivalent carbon emissions over the analysis period.